Influence of solar cycles on rainfalls in Azul, province of Buenos Aires - Vilatte, Carlos; Aguas, Laura; Confalone, Adriana (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
The aim of this paper was to find a synergism between maximum solar activity and rains in Azul, Buenos Aires (36°45' S, 59°57' W and altitude. 137 m ), using a series of annual rainfalls from 1913 to 2012. The results showed that the last four solar activity maxima correspond to the years of highest rainfall. Annual rainfalls for those years recorded on average 1317mm (2.4 standard deviation above the mean), which was significantly different from the mean of the last hundred years (855.7mm ±191.1 mm). A positive relationship between years of maximum solar activity and the occurrence of extreme rainfall events that generate excess water and flooding in the rural and urban sectors of Azul was found.